Newborn screening for spinal muscular atrophy: The views of affected families and adults. Issue 6 (4th April 2017) - Boardman, Felicity K.; Young, Philip J.; Griffiths, Frances E.
Abstract : Spinal muscular atrophy (SMA) is one of the leading genetic causes of infant death worldwide. However, due to a lack of treatments, SMA has historically fallen short of Wilson‐Jungner criteria. While studies have explored the acceptability of expanded newborn screening to the general public, the views of affected families have been largely overlooked. This is in spite of the potential for direct impacts on them and their unique positioning to consider the value of early diagnosis. We have previously reported data on attitudes toward pre‐conception and prenatal genetic screening for SMA among affected families (adults with SMA [ n  = 82] and family members [ n  = 255]). Here, using qualitative interview [ n  = 36] and survey data [ n  = 337], we report the views of this same cohort toward newborn screening. The majority (70%) of participants were in favor, however, all subgroups (except adults with type II) preferred pre‐conception and/or prenatal screening to newborn screening. Key reasons for newborn screening support were: (1) the potential for improved support; (2) the possibility of enrolling pre‐symptomatic children on clinical trials. Key reasons for non‐support were: (1) concerns about impact on the early experiences of the family; (2) inability to treat. Importantly, participants did not view the potential for inaccurate typing as a significant obstacle to the launch of a population‐wide screening program. This study underscores the need to include families affected by genetic diseases within consultations on screening. This is particularly important for conditions such as SMA which challenge traditional screening criteria, and for which new therapeutics are emerging.